PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT â€œ X â€œ (PERSERO) UNIT INDUK WILAYAH RIAU DAN KEPULAUAN RIAU - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at PT â€œXâ€ (Persero) Head Unit for Riau and Riau Islands, having its address at Jalan Musyawarah, Labuh Baru Barat, Pekanbaru. The purpose of this study was to determine the effect of supervision on the work discipline of employees of PT â€œXâ€ (Persero) Head Unit for Riau and Riau Islands Regions. The population in this study found 122 people with a sample of 56 people. The data used are primary and secondary data with analysis using simple linear regression. The results showed that the supervisory variable had a positive direction on work discipline, it can be seen in the simple linear regression equation, namely Y = 8.930 + 0.716X. And the supervisory variable has a significant effect on work discipline, namely the value of t_count 8.894 > from t_table 2.00488 or the value of Sig. < 0.05. The magnitude of the influence of the work environment on performance is 59.4 percent while the remaining 41.6 percent describes other variables not observed in this study.